2015
DOI: 10.1007/s10068-015-0145-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium chloride in combination with salicylic acid on post-harvest freshness of apples

Abstract: The effects of calcium chloride (CaCl 2 ) and salicylic acid (SA) alone and in combination against postharvest anthracnose rot on apples caused by Colletotrichum gloeosporioides were investigated, and influences on several quality and disease resistance related parameters were evaluated. Dipping in a solution of 5% CaCl 2 +5 mM SA for 10 min was the most effective approach to inhibit C. gloeosporioides both in vitro and in vivo. A combined CaCl 2 and SA treatment had the best efficacy for mitigation of the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…In our previous study, fresh‐cut papaya treated with HW‐Ca had high retention of ascorbic acid, suggesting that the beneficial effect of calcium was due to the heat‐induced higher penetration of calcium into the fruit, which prevented the loss of ascorbic acid during storage (Ayón‐Reyna et al, ). Similar results were also observed in apples infected with Penicillium expansum , Botrytis cinerea , or Colletotrichum gloeosporioides ; fruit with the lowest decay area had the highest ascorbic acid content (Sharma, Singh, & Pal, ; Zhao & Wang, ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…In our previous study, fresh‐cut papaya treated with HW‐Ca had high retention of ascorbic acid, suggesting that the beneficial effect of calcium was due to the heat‐induced higher penetration of calcium into the fruit, which prevented the loss of ascorbic acid during storage (Ayón‐Reyna et al, ). Similar results were also observed in apples infected with Penicillium expansum , Botrytis cinerea , or Colletotrichum gloeosporioides ; fruit with the lowest decay area had the highest ascorbic acid content (Sharma, Singh, & Pal, ; Zhao & Wang, ).…”
Section: Resultssupporting
confidence: 65%
“…In our previous study, fresh-cut papaya treated with HW-Ca had high retention of ascorbic acid, suggesting that the beneficial effect of calcium was due to the heat-induced higher penetration of calcium into the fruit, which prevented the loss of ascorbic acid during storage (Ayón-Reyna et al, 2015). Similar results were also observed in apples infected with Penicillium expansum, Botrytis cinerea, or Colletotrichum gloeosporioides; fruit with the lowest decay area had the highest ascorbic acid content (Sharma, Singh, & Pal, 2013;Zhao & Wang, 2015). At the beginning of the storage, the total phenolics content of papaya fruits was 0.23 g GAE/kg FW and this parameter remained the same for all treated fruits (Figure 2b), value that agreed with the previously reported by Madani, Mirshekari, and Yahia (2016).…”
Section: Bioactive Compoundssupporting
confidence: 66%
See 1 more Smart Citation
“…Untreated pears showed higher acidity (2.20 ± 0.12 g malic acid L −1 ) than treated pears (1.73 ± 0.18 g malic acid L −1 ). In contrast, Zhao & Wang demonstrated that dipping apples in a solution of 5% CaCl 2 for 10 min moderated the decrease in titratable acidity values. Liu et al showed that apricots treated with 1% or 3% CaCl 2 for 2 min and stored at 5 °C had a higher TA than the control, and the decrease in TA was slower than in the control.…”
Section: Resultsmentioning
confidence: 87%
“…There were no significant differences (P > 0.05) in TPC or AA of whole pears after 8 months of storage (Table ). Zhao & Wang also reported that there were no significant differences (P > 0.05) in TPC between whole apples dipped in a solution containing 5% CaCl 2 and untreated samples after 28 d of storage (20 °C). Nevertheless, Kou et al observed that ‘Huangguan’ pears treated with 2% CaCl 2 showed higher values of phenolic compounds than untreated samples after 8 months of storage at 0 °C.…”
Section: Resultsmentioning
confidence: 97%